2021
DOI: 10.1155/2021/6630904
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Development towards Sustainability in Northwest China: Efficiency Assessment, Spatial‐Temporal Differentiation Characters, and Influencing Factors

Abstract: For achieving the sustainable development goals, green development has been raised to a high position for cities in China. The economic development in Northwest China is slow, the ecological environment is fragile, and the mineral resources are rich. Only through green development can we realize the comprehensive income of regional production development, rich life, and good ecology. This paper measures the green development efficiency of 30 prefecture-level cities in Northwest China by using DEA-SBM model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The provincial governments actively use administrative power to coordinate the development of the provincial economy and have achieved certain results. From the perspective of the whole northwest region, the coordinated development effect among provinces is weak, and the urban agglomeration has not effectively exerted its driving effect [ 52 ]. In addition, the development among provinces has a competitive effect, which will hinder the effective circulation of resources and technologies between neighboring provinces, resulting in the development of each province being dependent on its own resource endowment, and the differences among provinces are increasing year by year.…”
Section: Discussionmentioning
confidence: 99%
“…The provincial governments actively use administrative power to coordinate the development of the provincial economy and have achieved certain results. From the perspective of the whole northwest region, the coordinated development effect among provinces is weak, and the urban agglomeration has not effectively exerted its driving effect [ 52 ]. In addition, the development among provinces has a competitive effect, which will hinder the effective circulation of resources and technologies between neighboring provinces, resulting in the development of each province being dependent on its own resource endowment, and the differences among provinces are increasing year by year.…”
Section: Discussionmentioning
confidence: 99%
“…Undesirable outputs consist of environmental pollution and air pollution, indicated by carbon dioxide emissions and average PM2.5 levels in each county. A specific index system [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] is illustrated in Fig. 2 .…”
Section: Methods Index Selection and Data Sourcesmentioning
confidence: 99%
“…Xiang et al (2021) investigated the influencing factors of GDE of the paper industry in the Yangtze River Economic Belt, and found that the scale of enterprises, technological investment, and industrial structure had significant positive impact on GDE, yet environmental regulations and the intensity of foreign investment had significant negative impact. Si et al (2021) conducted research through 30 prefecture-level cities in Northwest China, and found that economic development, population density, traffic conditions, and education investment can significantly improve the urban GDE; however, the proportion of industries significantly hindered GDE improvement. Zhou et al (2020) found that the economic strength, industrial structure, openness, and climate conditions positively promoted urban GDE in China.…”
Section: The Influencing Factors Of Green Developmentmentioning
confidence: 99%